Daya Hambat Ekstrak Daun Sirih dan Daun Legundi Terhadap Pertumbuhan Bakteri Staphylococcus aureus - Ida Bagus Oka Suyasa; Heri Setiyo Bekti; Luh Putu Rinawati; Luh Putu Laksmi; Putu Diah Wahyuni; Desak Gede Dwi Agustini; Aprilia Rakhmawati (Universitas Muhammadiyah Surabaya, 2022)
Staphylococcus aureus is one of the causes of infectious disease, ranging from mild to severe infections such as meningitis. The drug that is often used is the penicillin class of antibiotics. Apart from chemical antibiotics, natural antibacterial compunds from plants can be also used as an alternative treatment for this infection. Such as green betel (Piper betle L.) and legundi (Vitex trifolia L.). The ethanol extract of betel leaf has antibacterial activity against Staphylococcus aureus. The phytochemical content in legundi leaf is also able to inhibit the growth of Staphylococcus aureus. The ethanol extract of betel leaf and legundi is made through a maceration process. The extract concentrations used in this study were 20%, 30%, and 40%. The inhibition test of Staphylococcus aureus using the disc method. From the results of this study, the active substances found in betel leaf were flavonoids, tannins, and phenols, while in legundi were found flavonoids, tannins and phenols, and quinones. In total, the mean inhibition zone in this study ranged from 7.87mm to 17.33mm where legundi leaf extract was in the moderate category, betel and combination extract were classified as strong. There was a difference in the diameter of the inhibition zone of betel and legundi extract at a concentration 20% with 40%. In the combination extract there is a difference in the concentration of 20% with 40% and 30% with 40%. An antimicrobial compound can be said to synergize if a mixture of two or more antimicrobial compounds is able to provide an effect of each compounds. In this study, it has seen that the mean of the combination is higher than the mean of legundi leaf extract. Meanwhile, the mean of betel leaf extract is still greater than the combination extract.